2020
DOI: 10.37036/ahnj.v6i1.157
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Yang Mempengaruhi Fetal Distress Pada Sectio Caesarea Di RSUD Banyumas

Abstract: Fetal distress is a disease that is very dangerous for the fetus because it can dispute a dangerous disease. It is a causative factor in which sectio caesarea is taken. Objective To fetal distress in section caesarea in RSUD (Regional Public Hospital) Banyumas. This research is was a Documentation Analysis using a Retrospective approach. The sampling technique with a total sampling of 80 respondents. The analysis was statistical descriptive. Most of the respondents 63 (78.8%) are in the reproductive period, 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
1
0
7
Order By: Relevance
“…The results of Muhammad's research (2016) showed that the indications that caused the incidence of sectio caesarea (SC) were 18 (20.7%) fetal position abnormalities, the highest was due to fetal distress as many as 25 (28.7%) and the lowest was due to fetal distress. birth of twins as much as 2 (2.3%) (Daryanti, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The results of Muhammad's research (2016) showed that the indications that caused the incidence of sectio caesarea (SC) were 18 (20.7%) fetal position abnormalities, the highest was due to fetal distress as many as 25 (28.7%) and the lowest was due to fetal distress. birth of twins as much as 2 (2.3%) (Daryanti, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…9 Hasil penelitian ini sesuai dengan penelitian yang dilakukan Daryanti di RSUD Banyumas, menyatakan bahwa gawat janin disebabkan persalinan lama dan kegagalan induksi persalinan. 10 Persalinan yang terlalu lama bukan hanya dapat menguras tenaga, tapi juga berbahaya bagi kondisi ibu dan janin di dalam kandungan. 10 Kondisi persalinan lama dapat menyebabkan kurangnya pasokan oksigen pada janin sehingga berisiko menyebabkan gawat janin.…”
Section: Cunclassified
“…10 Persalinan yang terlalu lama bukan hanya dapat menguras tenaga, tapi juga berbahaya bagi kondisi ibu dan janin di dalam kandungan. 10 Kondisi persalinan lama dapat menyebabkan kurangnya pasokan oksigen pada janin sehingga berisiko menyebabkan gawat janin. 10 Persalinan induksi juga merupakan faktor risiko gawat janin karena risiko dari induksi, yaitu kontraksi rahim yang terlalu kuat.…”
Section: Cunclassified
See 2 more Smart Citations